Language impairments in children with developmental language disorder and children with high-functioning autism plus language impairment: Evidence from Chinese negative sentences - Dai, Huilin; He, Xiaowei; Chen, Lijun; Yin, Chan (Frontiers in Psychology, 2022)
It is controversial about whether children with developmental language disorder (DLD) and those high-functioning autism plus language impairment (HFA-LI) share similar language profiles. This study investigated the similarities and differences in the production of Chinese negative sentences by children with DLD and children with HFA-LI to put evidence on this controversy. The results reflect a general resemblance between the two groups in their lower-than-TDA (typically developing age-matched) performance. Both groups encountered difficulties in using negative markers, which suggests that they might be impaired in feature agreement. Meanwhile, important differences were detected between the two groups. Specifically, children with HFA-LI displayed some characteristic performance. They showed stereotyped language in two similar negative structures, produced many non-target negative sentences that matches one single scene of a dynamic process, and demonstrated preference for an affirmative sentence over a negative one. This study supports the idea of common symptomatology of the two disorders. More importantly, it suggests that these two disorders, DLD and HFA-LI, are not altogether the same in language impairment and labels should not be simply attached to any children with language disorders. Instead, untypical language is very worthy of further analysis for the categorization of language disorders.